On quasi-ideals and bi-ideals in ternary semirings. (30th November 2005) - Kar, S.
Abstract : We introduce the notions of quasi-ideal and bi-ideal in ternary semirings and study some properties of these two ideals. We also characterize regular ternary semiring in terms of these two subsystems of ternary semirings.